A mind in prison : the memoir of a son and soldier of the Third Reich - Manz, Bruno 1921- (Brassey's, 2000)
"A Mind in Prison is a candid autobiographical examination of life in Nazi Germany and the powerful hold Nazi propaganda had on Germany's youth. It is rare to find such an eloquent, frank, and truly remorseful account of the Nazi years by a German who made the tragic mistake of following Adolf Hitler."